Prison City: redesigning Pollsmoor Prison - Pullukattu, Liz (School of Architecture, Planning and Geomatics, 2018)
Rehabilitating the Prison System: The prison system in South Africa is a harsh and ineffective system that emphasises the need to punish rather than rehabilitate and reintegrate the incarcerated back into society. Although a lot of prisons in South Africa host a number of workshops and activities which have been introduced to inmates for such purposes- the recidivism rates of offenders, that have ended up in the penal system, has failed to drop or decline. A Process of deconstruction and synthesis: The method of this study is to analyse and deconstruct existing prison or correctional/ penitentiary/ rehabilitation institute landscapes into potential design components and then synthesise these into environments that can promote the rehabilitation of prisoners. The projects analysed are of international and South African origin, and are of prisons or mental and other high-security institutions. The analysed projects will be looked at as potential interventions that can be synthesised within the landscapes (rather, lack of landscapes) of Pollsmoor Prison in Cape Town. Looking into redesigning Pollsmoor Prisona prison where conditions do not support opportunities for rehabilitation and integration and where bland, cold concrete and brick facades enclose inmates for mostly 23-hours a day.